Unveiling a rarity: myoepithelial neoplasms of soft tissue - Abd. Fuaat, Azliana; Tuan Sharif, Sharifah Emilia; Hamdan, Asmah Hanim; Ahmad Affandi, Khairunisa; Azmi, Siti Nurhanisah (Academy of Medicine Malaysia, 2024)
Introduction: Myoepithelial neoplasms of soft tissue represent a heterogeneous group of tumours classified as benign (myoepithelioma and mixed tumour) or malignant (myoepithelial carcinoma). Case Presentation: We report the case of a 42-year-old woman with no prior medical conditions who presented with a right arm mass persisting for 15 years. Despite its gradual increase in size, she remained asymptomatic. Examination revealed a substantial mass in her right arm, with well-defined borders, a soft to firm texture, and a smooth surface covered by normal skin. MRI of the right humerus showed a lobulated solid-cystic mass, predominantly cystic, at the postero-medial aspect of the proximal humerus, measuring 7.1 × 7.6 × 11.5 cm. The mass was surgically excised. Gross examination revealed a well-circumscribed, lobulated-brownish mass measuring 120 × 80 × 60 mm. Cut section showed a mixture of solid and cystic components, with the solid areas displaying a brownish surface without necrosis. The cystic areas were multiloculated, ranging from 1-5 mm in diameter, and contained brownish fluid. Microscopic and immunohistochemical analysis indicated features of a myoepithelial neoplasm of soft tissue. Discussion: Myoepithelial neoplasms of soft tissue exhibit a spectrum of morphologic patterns, making them difficult to distinguish from other neoplasms. There are no definitive criteria for malignancy for this tumour. While most morphologically benign myoepithelial neoplasms of soft tissue behave in a benign manner, there is approximately a 20% risk of local recurrence. Therefore, complete excision with clear margins is crucial. Conclusion: Recognition of this rare tumour is essential for planning management and predicting prognosis.